THE CHANGING FACE OF “RELEVANCE” IN SOUTH AFRICAN PSYCHOLOGY - Long, Wahbie; Foster, Don (PINS-Psychology in Society, 2025)
For several decades, psychology in South Africa has been accused of lacking “relevance” insofar as the country’s social challenges are concerned. In this paper, the historical and discursive contours of this phenomenon known as the “relevance debate” are explored. Since the notion of “relevance” entails an assessment of the relationship between psychology and society, the paper presents the results of discursive and social analyses of forty-five presidential, keynote and opening addresses delivered at annual national psychology congresses between 1950 and 2011. These analyses reveal the close connection between discursive practices and social matrices, and, in particular, the post-apartheid emergence of a market discourse that now rivals a longstanding discourse of civic responsibility. This has created a potentially awkward juxtaposition of market relevance and social relevance in a nation still struggling to meet transformation imperatives